(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
In in vitro culture, LED light sources have replaced standard luminescent lamps and have acquired an important role in micropropagation. The effect of LED light on the development of four potato varieties in vitro was studied. The test was carried out in the INIA-Lara in vitro culture laboratory, the varieties used were María Bonita, Atlantic Dalinia and Kennebec. These were placed under photoperiod conditions of 8 hours in darkness and 16 hours with artificial LED light (illumination of 150-163 μmol m-2 s-1) and with an average temperature of 23 ± 2 ºC. The design used was completely randomized with 4 treatments with 5 repetitions of 5 bottles for each one. The in vitro characterization was considered by evaluating the morphological characteristics, length of the vitroplant and the root system, the number of leaves and the diameter of the stem. The LED light source is suitable for potato micropropagation, since good growth and development was observed in the evaluated varieties. Regarding the height of the seedlings, the Atlantic variety presented greater development. On the other hand, the length of the roots was greater in the Kennebec and Atlantic varieties while the Dalinia variety presented the lowest values. Kennebec developed a greater number of leaves, while Dalinia. María Bonita and Atlantic developed statistically equivalent values ​​and finally Kennebec and Atlantic produced thicker stems except Dalinia and María Bonita who produced thinner stems.